Khias Ventures : Copper Pot / Syahida Nafisah Mohd Radzi...[et al.] - Mohd Radzi, Syahida Nafisah; Mohd Razif, Mohammad Haziq; Amil, Izzat Nazmi; Mohd Rusdi, Muhammad Anas; Mohd Arsad, Khairul Nazim (2019)
Our company, KHIAS Venture is providing and producing a product called copper pot to start a business. We are providing three size of copper pot and also in set which in combo A and combo B which concern about problem that farmers had. Our objectives are to help farmers and planters to overcome one of their most problem. We intend to introduce our services to our prospect and customers by first, services strategy which are product attributes, trade name, brand name, and warranty and also after sale service. Second, price strategy are based on cost and based on competition. Third, promotion strategy has three modes of promotion which are advertising of printed media such as brochure, advertising signboard, newspaper advertisement, and magazines. Other than that, electronic media such as Facebook, Twitter, Instagram, Website, television programs, radios, and also outdoor advertisement like banner and signboard would use as one of our initiative.